The Influence of Work Competence and Work Environment on Employee Performance at PT Bank Mandiri Tbk Kerom Papua Branch with Job Satisfaction as a Mediating Variable - Fauziah; Cecep Yoto Haryoto (Paradoks : Jurnal Ilmu Ekonomi, 2025)
This study aims to analyze the influence of work competence and work environment on employee performance with job satisfaction as a mediating variable. While competence and the work environment are independent variables, employee performance is a dependent variable. The mediating variable is job satisfaction. 150 employees of the Kerom Branch of PT Bank Mandiri Tbk in Papua were given questionnaires to complete in order to gather data for the study. In this work, an associative research methodology was combined with a quantitative technique. The Partial Least Squares (SmartPLS)-based Structural Equation Modeling (SEM) method was used to analyze the data. Both skill (coefficient = 0.462) and the work environment (coefficient = 0.389) positively and significantly affect job satisfaction. Additionally, the work environment (coefficient of 0.198) and competence (coefficient of 0.172) both significantly and favorably affect employee performance. Employee performance is significantly and favorably impacted by work satisfaction, as seen by its 0.321 value. Additionally, both competence (coefficient of 0.236) and work satisfaction (coefficient of 0.217) have a significant and positive impact on employee performance.